The Influence of Accounting Understanding, Accounting Digitalization, and Human Resource Competence on the Quality of Financial Reports in Village Credit Institutions in Ubud District - Ni Putu Intan MELANI; Komang Adi Kurniawan SAPUTRA; Ida Ayu SURASMI (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to determine the influence of accounting understanding, accounting digitalization, and human resource competence on the quality of financial reports at Village Credit Institutions in Ubud District. This research uses a quantitative approach with a population of 32 Village Credit Institutions in the Ubud District. The sampling technique used in this research is a saturated sampling technique (census) which aims to minimize and reduce the level of error in data collection so that the number of samples in this research is 32 Village Credit Institutions in the Ubud District area. The unit of analysis for this research is the organization represented by the head of the Village Credit Institution. The data collection method in this research uses a questionnaire method with multiple linear regression analysis techniques. The research results show that understanding accounting, digitalization of accounting, and human resource competency each have a significant positive effect on the quality of financial reports at Village Credit Institutions in Ubud District.